2015
DOI: 10.1063/1.4917261
|View full text |Cite
|
Sign up to set email alerts
|

Biocellulose-based flexible magnetic paper

Abstract: Biocellulose or bacterial cellulose (BC) is a biocompatible (nano) material produced with a three-dimensional network structure composed of microfibrils having nanometric diameters obtained by the Gluconacetobacter xylinus bacteria. BC membranes present relatively high porosity, allowing the incorporation or synthesis in situ of inorganic nanoparticles for multifunctional applications and have been used as flexible membranes for incorporation of magnetic nanocomposite. In this work, highly stable superparamagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…This protocol focuses on the design of a bacterial nanocellulose-magnetic nanoparticle pellicle, which we have named magnetic bacterial nanocellulose (MBNC), which is intended to use as a substitute for missing, damaged or injured small-diameter blood vessels. H. S. Barud and coworkers have recently published a similar work to produce a BNC-based flexible magnetic paper by mixing BNC pellicles in a stable aqueous dispersion of PEG and superparamagnetic iron oxide nanoparticles 3 . Here, we describe the production of bacterial cellulose and its impregnation in situ with magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…This protocol focuses on the design of a bacterial nanocellulose-magnetic nanoparticle pellicle, which we have named magnetic bacterial nanocellulose (MBNC), which is intended to use as a substitute for missing, damaged or injured small-diameter blood vessels. H. S. Barud and coworkers have recently published a similar work to produce a BNC-based flexible magnetic paper by mixing BNC pellicles in a stable aqueous dispersion of PEG and superparamagnetic iron oxide nanoparticles 3 . Here, we describe the production of bacterial cellulose and its impregnation in situ with magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…This type of hybrid is known as a magnetic-BC nanohybrid, and it can be used in several applications, such as filtration or purification, toxic waste remediation, and loudspeaker membranes. Recently, Barud et al (2015) incorporated PEG-Fe2O3 magnetic nanoparticles into BC membranes, and the resulting hybrid presented magnetic behavior as expected. The MFM (magnetic force microscopy) phase images of the BC-Fe2O3 membrane confirmed that the nanoparticles retained their magnetic properties among the BC nanofibers network (Barud et al 2015).…”
Section: Bc-based Nanocomposites Silver Particles and Self-assemblementioning
confidence: 99%
“…Recently, Barud et al (2015) incorporated PEG-Fe2O3 magnetic nanoparticles into BC membranes, and the resulting hybrid presented magnetic behavior as expected. The MFM (magnetic force microscopy) phase images of the BC-Fe2O3 membrane confirmed that the nanoparticles retained their magnetic properties among the BC nanofibers network (Barud et al 2015). Carbon paper has both excellent conductivity and permeability.…”
Section: Bc-based Nanocomposites Silver Particles and Self-assemblementioning
confidence: 99%
See 2 more Smart Citations